Serum levels of G protein-coupled estrogen receptor 1 (GPER1) in drug-naive patients with generalized anxiety disorder. (30th October 2016) - Fındıklı, Ebru; Camkurt, Mehmet Akif; Karaaslan, Mehmet Fatih; Kurutas, Ergul Belge; Altun, Hatice; İzci, Filiz and Fındıklı, Hüseyin Avni and Kardas, Selçuk
Abstract: Sex hormones, particularly estrogen, are suggested to play a role in the physiopathology of generalized anxiety disorder (GAD). Estrogen functions through the estrogen receptors alpha and beta and the recently discovered G protein-coupled estrogen receptor 1 (GPER1). This study aimed, for the first time, to evaluate serum GPER1 levels in drug-naive patients with GAD. This study included 40 newly diagnosed drug-naive patients with GAD aged between 18 and 50 years and 40 age- and gender-matched healthy controls. Medical histories were obtained, and physical examinations and laboratory tests were conducted; the Hamilton Anxiety Rating Scale (HAM-A) was also used for all participants. Serum GPER1 levels were measured. The serum GPER1 level was significantly higher in the patients with GAD than in the controls. A positive significant correlation was observed between the GPER1 level and the HAM-A score. The receiver operating characteristic analysis revealed a sensitivity, specificity, positive predictive value, and negative predictive value of 85.0%, 82.5%, 82.9%, and 84.6%, respectively, for the presence of anxiety when the serum GPER1 value was ≥0.14 (the area under the curve was 0.904.). In conclusion, this study demonstrated that GPER1 levels were associated with the anxiety levels of patients, and that the serum GPER1 level was a valuable predictor of the presence of anxiety independent of gender. Highlights: GPER1 levels were found to be increased in drug-naïve patients with generalized anxiety disorder. GPER1 levels showed a positive correlation with the Hamilton Anxiety Scale scores of patients. GPER1 might be a candidate peripheral biomarker for generalized anxiety disorder.